Analysis of Internal and External Efficiency Through the Value for Money Model in Educational Institutions: A Case Study at SDN Jombor, Jumo District, Temanggung Regency - Wahyuningsih, Sri; Istiqomah; Kusumastuti, Anggun Fauziana; Nurkolis (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the internal and external efficiency of educational institutions through the Value for Money approach at SDN Jombor, Jumo District, Temanggung Regency. Value for money serves as a performance evaluation model that focuses on three leading indicators: economy, efficiency, and effectiveness in managing educational resources. This research employs a qualitative approach, utilizing a case study method. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed descriptively. The findings indicate that the school has attempted to implement the principles of economy in budget management, efficiency in the use of human and material resources, and effectiveness in achieving educational objectives. However, several challenges remain, such as the lack of teacher training and limited internal supervision. The novelty of this study lies in its application of the Value for Money framework within the context of public primary schools, a context that is still rarely explored empirically. This research makes a theoretical contribution to the development of value-based evaluation models in educational management and a practical contribution to formulating policies that enhance transparency, accountability, and the quality of education services at the elementary school level.